2016
DOI: 10.3991/ijet.v11i03.5100
|View full text |Cite
|
Sign up to set email alerts
|

Webquest-Based Role Play as a Way of Raising Students’ Motivation to Studying Foreign Languages

Abstract: Abstract-Teaching English as a foreign language using modern Internet technologies is considered in the paper. A special attention is paid to the Webquest-based role play organized by means of up-to-date Internet technologies as an approach to raise technical students' motivation to studying foreign languages. Emphasis is upon applying this approach to organizing conference weeks at National Research Tomsk Polytechnic University (TPU). An overview of the Webquest-based role play activities is also given in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Results revealed that the H-PBL approach has a positive effect on improving the students' speaking proficiency, students' motivation significantly increased and, eventually, students tended to be more self-directed and independent. Instructors also applauded the use of H-PBL approach but recommended adapting the curriculum and the teaching Sumtsova et al (2016) conducted a study to improve motivation using web quest. A special attention is paid to the web quest-based role play organized by means of up-to-date Internet technologies as an approach to raise technical students' motivation to studying foreign languages.…”
Section: Literature Review and Related Studiesmentioning
confidence: 99%
“…Results revealed that the H-PBL approach has a positive effect on improving the students' speaking proficiency, students' motivation significantly increased and, eventually, students tended to be more self-directed and independent. Instructors also applauded the use of H-PBL approach but recommended adapting the curriculum and the teaching Sumtsova et al (2016) conducted a study to improve motivation using web quest. A special attention is paid to the web quest-based role play organized by means of up-to-date Internet technologies as an approach to raise technical students' motivation to studying foreign languages.…”
Section: Literature Review and Related Studiesmentioning
confidence: 99%
“…«In a modern society, knowledge of foreign language is vital for people intending to do well in the area of their professional activity» (Sumtsova, Azhel,  Buyankina, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Practice-oriented studies into motivation are devoted to investigation of the role of some didactic methods as reading [10], writing [11], role plays [12], flipped classroom method [13], etc. in raising the level of academic motivation.…”
Section: Methodsmentioning
confidence: 99%